Isothermal titration calorimetry uncovers substrate promiscuity of bicupin oxalate oxidase from Ceriporiopsis subvermispora - Hassan Rana; Patricia Moussatche; Lis Souza Rocha; Sofiene Abdellaoui; Shelley D. Minteer; Ellen W. Moomaw (Biochemistry and Biophysics Reports, 2016)
Isothermal titration calorimetry (ITC) may be used to determine the kinetic parameters of enzyme-catalyzed reactions when neither products nor reactants are spectrophotometrically visible and when the reaction products are unknown. We report here the use of the multiple injection method of ITC to characterize the catalytic properties of oxalate oxidase (OxOx) from Ceriporiopsis subvermispora (CsOxOx), a manganese dependent enzyme that catalyzes the oxygen-dependent oxidation of oxalate to carbon dioxide in a reaction coupled with the formation of hydrogen peroxide. CsOxOx is the first bicupin enzyme identified that catalyzes this reaction. The multiple injection ITC method of measuring OxOx activity involves continuous, real-time detection of the amount of heat generated (dQ) during catalysis, which is equal to the number of moles of product produced times the enthalpy of the reaction (ΔHapp). Steady-state kinetic constants using oxalate as the substrate determined by multiple injection ITC are comparable to those obtained by a continuous spectrophotometric assay in which H2O2 production is coupled to the horseradish peroxidase-catalyzed oxidation of 2,2′-azinobis-(3-ethylbenzthiazoline-6-sulfonic acid) and by membrane inlet mass spectrometry. Additionally, we used multiple injection ITC to identify mesoxalate as a substrate for the CsOxOx-catalyzed reaction, with a kinetic parameters comparable to that of oxalate, and to identify a number of small molecule carboxylic acid compounds that also serve as substrates for the enzyme.